Distribution sector reforms in India: the tasks ahead. (21st April 2005) - Thakur, Tripta
The distribution sector is the focus of the ongoing power reforms in India, mainly due to its key role in realising the sales proceeds and, therefore, in ensuring the financial viability of the entire power sector. This paper details some of the problems plaguing the distribution sector and spells an overview of the various efforts and the reform measures initiated by the government of India to ensure that the sector becomes financially and operationally viable. This paper also discusses some of the important areas where certain issues need to be addressed by the policy makers to ensure that the distribution sector becomes efficient. The paper discusses these issues that include reorganisation of the distribution sector through optimal zoning, the issue of efficiency measurement through benchmarking of distribution utilities, privatisation-related aspects, the role of regulatory commissions, implementation of Multi-Year Tariff framework, and the need for universal metering.